Transfer of transition-metal dichalcogenide circuits onto arbitrary substrates for flexible device applications - Lee, Hyebin; Lee, Kookjin; Kim, Yanghee; Ji, Hyunjin; Choi, Junhee; Kim, Minsik; Ahn, Jae-Pyoung; Kim, Gyu-Tae (ROYAL SOC CHEMISTRY, 2019)
Transition-metal dichalcogenide (TMD) materials with two-dimensional layered structures and stable surfaces are well suited for transparent and flexible device applications. In order to completely utilize the advantages of thickness control and fabrication of various heterostructure stacks, we proposed a transfer method of TMD field-effect transistors (FETs) and TMD complementary metal-oxide-semiconductor (CMOS) circuits from a Si/SiO2 substrate to a flexible substrate. We compared the characteristics of transferred MoS2 and WSe2 FETs with those of the corresponding devices transferred after channel passivation with an Al2O3 layer on a flexible substrate. Al2O3 passivation further stabilized the transfer of the entire device with electrodes. A CMOS circuit with MoS2 and WSe2 materials could be successfully transferred to a polyethylene terephthalate substrate after the channel passivation. This implies that TMD circuits can be easily fabricated on polymer substrates, which makes them suitable for use in semiconductor processes, for various applications.
Keywords: HIGH-PERFORMANCE; ROOM-TEMPERATURE; MOS2 TRANSISTORS; EXFOLIATION; FILMS